Design and Implementation of Augmented Reality Browser for Mobile Terminal. Issue 3 (April 2019) - Li, Dan; Shang, Yanlei
Abstract: The rapid advancement of mobile internet technology has promoted the vigorous development of Augmented Reality (AR) applications. However, the native AR application on the mobile terminal has the disadvantages of closedness and high cross-platform cost. The Web-based application has universality and good cross-platform characteristics. Using Web as the carrier of AR applications will solve the problems of the native application. However, there is a large gap between Web applications and the native applications in the performance and efficiency of the algorithm. To solve these problems, the mobile browser's support for AR applications has been expanded in this paper. The native computing ability of the mobile phone is encapsulated into a Web-callable interface, and the hybrid rendering method is used which uses both the native and the Web to render the AR applications.